Trends in dental-related visits to a tertiary hospital emergency department in Saudi Arabia - Raghad A Alammar; Nada A Alsulaiman; Moath A Alabdullatif; Abdullah M Alwhaibi; Lubna T Alkadi (Wolters Kluwer Medknow Publications, 2021)
Introduction: Emergency medicine department visits for odontalgia, related to traumatic and non traumatic dental events has seen a shift towards increase in cases. Emergency departments provide palliative care especially for the non traumatic dental injuries Aims: To explore the trends of emergency department (ED) visits for dental-related conditions in Saudi Arabia. The study also aimed to analyze visit management patterns, including procedures, prescriptions, and recall visits. Materials and Methods: A cross-sectional retrospective observational study was done using simple random sampling on dental emergency visit data to the ED at hospitals under renowned university of health sciences in Riyadh and Al-Ahsa between January 2016 and May 2019. Results and Discussion: A total of 5050 charts were included. An increase in dental emergency visits was observed between 2016 and 2017. Pulpal and periapical lesions were the most frequently diagnosed conditions every year (53.83% of all dental-related ED visits), and traumatic injuries were the least frequently (6.37%) diagnosed condition. Conclusion: Dental-related visits to EDs in Saudi Arabia increased remarkably from 2016 to 2019. Pulpal and periapical conditions were the most frequent cause of dental-related ED visits. To ensure better use of ED time and resources, it is imperative to raise public awareness of what types of urgent dental conditions require an ED visit, as well as to increase the number of public health unit dental clinics and their ease of access.